Large-Scale 3D Printing for Construction Application by Means of Robotic Arm and Gantry 3D Printer: A Review - Anastasia Puzatova; Pshtiwan Shakor; Vittoria Laghi; Maria Dmitrieva (Buildings, 2022)
Additive manufacturing technologies are becoming more popular in various industries, including the construction industry. Currently, construction 3D printing is sufficiently well studied from an academic point of view, leading towards the transition from experimental to mass large-scale construction. Most questions arise about the applicability of construction 3D printers for printing entire buildings and structures. This paper provides an overview of the different types of construction 3D printing technologies currently in use, and their fundamental differences, as well as some significant data on the advantages of using these advanced technologies in construction. A description of the requirements for composite printing is also provided, with possible issues that may arise when switching from lab-scale construction printing to mass large-scale printing. All printers using additive manufacturing technologies for construction are divided into three types: robotic arm printers, portal-type printers, and gantry 3D printers. It is noted that gantry printers are more suitable for large-scale printing since some of their configurations have the ability to construct buildings that are practically unlimited in size. In addition, all printers are not capable of printing with concrete containing a coarse aggregate, which is a necessary requirement in terms of the strength and economic feasibility of 3D printing material for large-scale applications.